A Systematic Literature Review of Virtual Reality for Teaching Individuals with Autism Spectrum Disorder: Review of Virtual Reality for Teaching - Jacob, Udeme Samuel (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2025)
This systematic literature review explores the application and efficacy of virtual reality as a tool for teaching and improving skills in individuals with autism spectrum disorder (ASD). Considering the heterogeneity of ASD and the importance of early intervention, it is imperative to identify effective, innovative therapeutic approaches. A comprehensive search of existing literature and research databases, including PubMed, PsycINFO, IEEE Xplore, Scopus and EBSCOhost, was undertaken, and 704 articles were identified as relevant. We evaluated these studies, establishing their eligibility, and eight met the inclusion criteria. This review synthesised studies highlighting the potential of virtual reality to address the unique needs of individuals with ASD, including social skills training, emotional and cognitive development and the management of specific phobias. It reveals how virtual reality simulations offer a safe and controlled environment for practice and learning, supporting the development of essential skills for social interaction and daily functioning. With its structured and individualised approach, virtual reality technology emerges as a promising intervention that caters to the diverse requirements of the ASD population. The review calls for further research to optimise virtual reality tools for broader clinical applications, aiming for more inclusive and accessible interventions for individuals with ASD.